Dissolved organic matter characterization of biochars produced from different feedstock materials. (1st March 2019) - Rajapaksha, Anushka Upamali; Ok, Yong Sik; El-Naggar, Ali; Kim, Hyojeon; Song, Fanhao; Kang, Seoktae; Tsang, Yiu Fai
Abstract: Fluorescence excitation-emission matrix (EEM) spectroscopy coupled with parallel factor analysis (PARAFAC) enables better understanding of the nature of dissolved organic matter (DOM). In the current study, we characterized 10 biochar samples produced from different feedstocks using EEM/PARAFAC analysis. The composition and distribution of DOM substances present in biochar varied significantly according to feedstock, activation, and pyrolysis temperature. The integration of proximate and ultimate analyses of the solid phase together with water extractable organic matter (WEOM) phase of biochar provided new insights into the characterization of biochars, including nature and functionality. Characterization of both WEOM and solid phases is recommended for biochar research before large-scale production for various environmental and industrial applications. Highlights: 10 biochar samples produced from different feedstocks were characterized. Four fluorescent components were successfully identified in different biochars. Pyrolysis temperature, activation, and feedstock were the major factors affecting the presence of different DOM substances. Protein-/tannin-like component in biochar was mainly influenced by feedstock. Humic-like substances were mainly affected by pyrolysis temperature and activation.